2019
DOI: 10.4103/jfmpc.jfmpc_600_19
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among health care providers: A cross-sectional study in public health facilities of Punjab, India

Abstract: Introduction:Job satisfaction is a multidimensional response to work and workplace environment. It depends on many factors, and affects the behavior of employees that, in turn, affects organizational functioning. The aim of the study was to measure job satisfaction among different categories of healthcare providers from the Punjab government health services and to determine the factors that affect job satisfaction the most.Methodology:The study was conducted between September 2015 and February 2016 and include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
0
18
1
1
Order By: Relevance
“…Unfortunately, in the health sector, there is poor job satisfaction caused by low income, poor working conditions, and limited opportunities for career development within healthcare organizations (Hotchkiss et al, 2015). A recent study reported that 75.3% of health care workers were dissatisfied with their working environment, salary, promotion and benefits, whereas the relationships with leaders and co-workers were satisfaction factors (Verma et al, 2019). In an earlier study pay, promotion, training and development, relations with supervisors, poor working conditions and organizational policies were the main factors for job dissatisfaction among health workers in eastern Ethiopia (Geleto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in the health sector, there is poor job satisfaction caused by low income, poor working conditions, and limited opportunities for career development within healthcare organizations (Hotchkiss et al, 2015). A recent study reported that 75.3% of health care workers were dissatisfied with their working environment, salary, promotion and benefits, whereas the relationships with leaders and co-workers were satisfaction factors (Verma et al, 2019). In an earlier study pay, promotion, training and development, relations with supervisors, poor working conditions and organizational policies were the main factors for job dissatisfaction among health workers in eastern Ethiopia (Geleto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a study on job satisfaction among clinical and non-clinical hospital staff in a teaching hospital in Lagos, Nigeria reported that the majority of respondents were satisfied with their job (Coker & Coker, 2011). Studies in Vientiane reported 65.0%, (Khamlub et al, 2013) and Indian (66%) (Singh, Kaur, & Verma, 2019) job satisfaction among study respondents.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, another study in Ethiopia among healthcare workers at a teaching hospital reported motivation, inadequate salary, insufficient training opportunities, and an inadequate number of human resources were responsible for their dissatisfaction (Yami et al, 2011). "Motivating factors like pay, fringe benefits and contingent rewards need to be met for an employee to be satisfied with work" (Singh, Kaur, & Verma, 2019). Quality of services has been linked to skills, motivation, and satisfaction of healthcare workers and it has been documented about the factors affecting the satisfaction of healthcare workers that managers who devote their time to work are more likely to gain improved performance (Singh, Kaur, & Verma, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per this theory, when working atmospheres (factors of hygiene) are not strong, the worker is displeased, however, when these factors are strong or being better, it means the employee is not unsatis ed, but also not always satis ed. [3] Satisfaction during work can affect the attitude of employees which in uences organizational operations [4]. In general, humans have 3 sets of basic needs: relatedness, existence, and growth [5].…”
Section: Introductionmentioning
confidence: 99%